A safe house [large type] - Woods, Stuart (Woods, Stuart. Stone Barrington novel, 2022)
"Stone Barrington is looking forward to some quiet time in New York City, until he is asked to transport precious, top-secret cargo across the Atlantic. Taking on the challenge, Stone flies off unaware of what--or who--he is bringing with him. But his plans to lie low are quickly spoiled when a dangerous dispatcher tracks down Stone and his tantalizing mystery guest, intent on payback--and silencing anyone who poses a threat. From the English countryside to the balmy beaches of Key West, Stone is on an international mission to hide and protect those closest to him"--